ANALISIS TINGKAT KETERCAPAIAN TUJUAN PEMBELAJARAN SOSIOLOGI DIERA NEW NORMAL PADA SISWA KELAS XI IPS 2 SMAN 1 PAINANMAN 1 PAINAN - Sonia elisa trisnawati; Yenni Melia; Hefni Hefni (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
This study aims to see the level of achievement of the learning objectives of sociology in the new normal in class XI IPS 2 SMAN 1 Painan. The approach used in this research is descriptive quantitative method using survey method. Data collection techniques used in this study were learning outcomes test, observations, and document studies. The instrumen in this study used learning outcomes test and observatins shees. The data analysis technique used is the percentage. Based on the results of the study, it was found that the results of the analysis were related to the achievement of the learning objectives of sociology in the cognitive aspect was 46%, the achievement in the affective aspect with an overall indicator of  85%, and the achievement of learning objective in the psychomotor aspect with an overall indicator of  83%. From the persentage results it can be concluded that the achievement of the learning objectives of sociology in the new normal era in class XI IPS 2 SMAN 1 Painan, has not been achieved optimally especially in the cognitive aspect, were the achievement is still below 50% and included in the low category.